OCORRÊNCIA DE ÁCAROS Tenuipalpus heveae NA CULTURA DA SERINGUEIRA - GANZELLA, Luiza Guidi; TOSCANO, Luciana Cláudia; RIBEIRO, Brenda Luciana Queiroz; FERREIRA, Amanda Maria Frata; SILVA, Eduardo Paulino da Costa; OLIVEIRA, Matheus Rodrigues (ANAIS DO ENIC, 2024)
-